Methodological Approach to the Organization of Monitoring of Cash Flow Volatility - A. V. Larionov (Финансы: теория и практика)
The study presents the author’s approach to monitoring the volatility of cash flows. The relevance of the study is due to the fact that a high increase in volatility can have a negative impact on the stability of individual economic entities; therefore, central banks are faced with the task of organizing a system for monitoring cash flow volatility, as well as developing approaches to their regulation. The purpose of the study is to develop a methodological approach to organizing the monitoring of cash flow volatility. Statistical methods, including fractal analysis, are used in the study. The study determines the approach to classifying different levels of cash flow volatility. Three main types of cash flow — moderate, transient, and turbulent,—are defined. The study confirmed two hypotheses. First, it is proven that the volatility of cash flows is more the result of behavioural factors than institutional ones. Second, it is established that the turbulent type of cash flow occurs in more rare cases than the moderate or transient types. It is shown that the volatility of the cash flow is the result of behavioral reactions of economic entities to fluctuations in economic activity. Institutional factors determine the limits of cash flow volatility, but fluctuations within these limits are the result of the reaction of economic actors to changes in the external environment. The turbulent type of cash flows occurs during the period of simultaneous actions of all economic entities. Based on the three-sigma rule, a methodological approach to determine confidence intervals classifying cash flows by the type of movement was suggested.It is concluded that since the turbulent type of cash flows has the greatest negative impact on the stability of the economy, it should be of significant interest for monitoring and subsequent regulation by the Bank of Russia. A promising direction for further research may be the development by the Bank of Russia of a specialized refinancing instrument to compensate for the shortage of funds due to the increased level of cash flow volatility.